Natural History of 321 Flatfoot Reconstruction Patients Over a 14 Year Period Performed at a Single Institution. Issue 4 (16th October 2019) - Goss, Madison; Stauch, Chris; Lewcun, Joseph; King, Jesse; Fritsche, Madelaine; Juliano, Paul; Aynardi, Michael
Category: Midfoot/Forefoot Introduction/Purpose: Outcomes following surgical reconstruction for acquired flatfoot deformity secondary to posterior tibial tendon dysfunction have been well described. However, the majority of studies have a limited number of patients or short to mid- term follow-up. The purpose of this study was to report the natural history, demographics, and mechanisms of treatment failure for patients undergoing flatfoot reconstruction at a single institution by a single surgeon. Methods: With IRB approval, 321 consecutive patients undergoing flatfoot reconstruction during a 14-year period were included in this study (February 2002 through October 2016). All procedures were performed by a single surgeon (PJJ) at our institution. Demographic data, surgical data, clinic notes, and radiographs were available for review. Exclusion criteria included patients without electronic records or incomplete data. Failure was defined as a need to return to the operating room for revision surgery. Statistical analysis was performed. Results: 321 consecutive patients underwent flatfoot reconstruction from 2002-2016. The majority of patients were female (83.2%) with left laterality (58.6%) & a body mass index classified as overweight (21.5%) or obese (56.4%). 13.7% of patients were diabetics, and 18.4% were current smokers. 54 patients (16.8%) experienced treatment failure. Painful calcaneal hardware requiring removal occurred in 11.8% of patients, conversion to triple arthrodesis occurred in 3.45%, and wound complications or infection requiring irrigation & debridement occurred in 1.87%. There were no mortalities reported within 90 days. There were 3 symptomatic deep vein thromboses, none requiring surgical intervention, & no pulmonary embolisms. A significant increase in relative risk of treatment failure was calculated for female gender, current cigarette use, & age under 60 (3.4 p=0.0005/1.9 p=0.0081/1.8 p=0.042). Conclusion: This study represents the largest series of patients undergoing flatfoot reconstruction by a single surgeon at a single institution. Although retrospective, the results provide valuable insight to the natural history of patients undergoing this procedure. The overall complication rate and treatment failure rates are low and similar to those previously reported in the literature. Patients with female gender or under 60 years of age should be notified of their increased relative risk of treatment failure & counseled accordingly. Smoking cessation is recommended to reduce the risk of treatment failure.